Distribution and conservation status of fishes reported from muntjibpur pond of Allahabad (U.P.) - Verma, Ashok Kumar (International Journal of Scientific World, 2017)
Muntjibpur pond was studied to find out the conservation status of the fishes naturally occurring in it. The survey was conducted from July 2014 to June 2015. During exploration, a total of 13 species of fishes belonging to 12 genera, 8 families and 5 orders were identified. As per latest version of IUCN Red List, out of 13 species of fishes identified, 1 species comes under UV (vulnerable), 1 under NT (near threatened), 8 under LC (least concern) and 3 species are NE (not evaluated) so far. No fish species identified here comes under EN (endangered) category.